Silicic acid solution for undercoat of photocatalytic film, photocatalyst coating liquid, and member
An aqueous silicic acid solution with controlled composition and additives addresses the issues of uneven coating and poor durability in conventional binders, resulting in a uniform and transparent photocatalytic film with enhanced adhesion and water resistance.
Patent Information
- Application Number
- JP2023106562
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional silicon compound-based binders for photocatalytic films face issues with uneven coating, poor water resistance, and reduced photocatalytic activity, particularly when applied to substrates prone to deterioration due to photocatalytic action.
An aqueous silicic acid solution with specific silicic acid concentration, molar ratio of silicon to alkali, and viscosity, combined with a surfactant and optional additives, is used to create a uniform and highly transparent photocatalytic film with improved adhesion and water resistance.
The solution enables even coating and enhances the durability and transparency of photocatalytic films, ensuring effective photocatalytic performance on various substrates.
Smart Images

Figure 2025006028000001 
Figure 2025006028000002 
Figure 2025006028000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous silicic acid solution for use as an undercoat for a photocatalyst film, a photocatalyst coating liquid containing the aqueous silicic acid solution, and a member having a surface thereof coated with a coating film produced from the liquid. [Background technology]
[0002] In recent years, there has been a growing tendency among consumers to seek a hygienic living environment, and interest in daily necessities that have been treated to maintain cleanliness through antibacterial, antifungal, antiviral and anti-odor properties has increased.
[0003] Photocatalytic materials have attracted attention because they can provide a wide range of effects for cleaning the surface of substrates, including antibacterial, antifungal, antiviral, deodorizing, and antifouling properties, through the photocatalytic reaction that occurs when exposed to light such as sunlight or artificial lighting. Photocatalytic reaction refers to a reaction caused by excited electrons and holes generated by the absorption of light by a photocatalyst such as titanium oxide. The excited electrons and holes generated on the titanium oxide surface by the photocatalytic reaction cause an oxidation-reduction reaction with oxygen and water adsorbed on the titanium oxide surface to generate active species. Organic microorganisms, viruses, odors, and dirt are decomposed by these active species, so it is believed that the above-mentioned cleaning effect of the substrate surface can be obtained.
[0004] The active species produced by photocatalytic reactions basically act on any type of organic matter, so photocatalysis is effective against a wide variety of microorganisms, viruses, odors and dirt, and it hardly deteriorates over time. These are some of the advantages of photocatalysis.
[0005] Recently, applications of the above-mentioned photocatalytic action have been investigated not only for outdoor use where ultraviolet light (wavelength 10 to 400 nm) can be used, but also for indoor spaces illuminated by light sources such as fluorescent lamps where the majority of light is in the visible range (wavelength 400 to 800 nm). For example, a tungsten oxide photocatalyst (JP Patent Publication No. 2009-148700: Patent Document 1) has been developed as a visible light responsive photocatalyst.
[0006] In general, such photocatalysts are used by dispersing photocatalyst particles in a solvent, mixing with a binder (film-forming component) to form a coating liquid, and applying it to a substrate. A material that fixes the photocatalyst to the substrate and does not or is unlikely to deteriorate due to photocatalytic action is selected as the binder.
[0007] In addition, when forming a photocatalytic film on the surface of a substrate that is expected to deteriorate due to photocatalytic action, such as an organic substrate or a substrate coated with an organic paint, an undercoat (primer) layer is often provided between the substrate surface and the photocatalytic film in order to prevent deterioration of the substrate surface and improve the adhesion of the photocatalytic film. The performance required for the materials used in the binder and undercoat as described above is similar, so the same materials are often used.
[0008] As binders and undercoats that are less susceptible to deterioration due to photocatalytic action, those whose main component is an inorganic material are preferred. For example, a coating composition using an alkali metal silicate (JP Patent Publication No. 2001-098187: Patent Document 2) and an aqueous paint composition containing photocatalyst particles, an alkali metal silicate, and a weather-resistant resin emulsion (JP Patent Publication No. 2003-096394: Patent Document 3) have been disclosed; however, the former has problems such as poor water resistance, poor coatability and adhesion to organic substrates, and a high alkali component content that inhibits the dispersion stability of the photocatalyst particles, while the latter contains a resin emulsion, which results in problems such as inferior durability compared to inorganic materials alone, reduced photocatalytic functions such as hydrophilicity, and the resin emulsion and alkali components inhibiting the dispersion stability of the photocatalyst particles.
[0009] The present inventors also discovered that by using a coating liquid in which a silicon compound-based binder is added to titanium oxide particles having tin and a transition metal that enhances visible light activity in a solid solution and iron and silicon attached to the surface, a highly transparent photocatalytic film that exhibits higher photocatalytic activity than conventional films under visible light irradiation can be obtained (JP Patent Publication 2021-175697: Patent Document 4). However, depending on the coating method and substrate, the silicon compound-based binder can cause uneven application of the coating liquid, making it difficult to obtain a uniform coating film, or can have poor water resistance. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2009-148700 A [Patent Document 2] JP 2001-098187 A [Patent Document 3] JP 2003-096394 A [Patent Document 4] JP 2021-175697 A Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide an aqueous silicic acid solution to be used as a binder and undercoat for a photocatalyst, which can be uniformly applied to substrates and by coating methods that have been difficult with conventional silicon compound-based binders, and which can provide a film with high water resistance and transparency. [Means for solving the problem]
[0012] In order to achieve the above-mentioned object, the inventors have conducted detailed investigations into the raw materials and component ratios of silicon compound-based binders and undercoats, and have found that by using an alkali silicate in which the silicon to alkali molar ratio is specific, it is possible to form a highly uniform film even with coating methods and substrates that were previously difficult to use, and that the coating film also has excellent water resistance and transparency, which has led to the invention.
[0013] Therefore, the present invention provides an aqueous silicic acid solution, a coating film formed using the aqueous silicic acid solution, a member having a coating film on its surface, and a method for producing the aqueous silicic acid solution, all of which are described below. [1] Contains an alkali silicate and an aqueous solvent, Silicic acid concentration (SiO2 equivalent): 0.1 to 3 mass% Molar ratio of silicon (SiO2 equivalent) to alkali X (SiO2 / X): 85-10,000 Viscosity at 25℃ is 1 to 50 mPa s This is an aqueous solution of silicic acid used as an undercoat for photocatalytic membranes. [2] The aqueous silicic acid solution according to [1], further comprising a surfactant. [3] The aqueous silicic acid solution according to [1] or [2], wherein the aqueous solvent is a mixed solvent of water and a hydrophilic organic solvent. [4] A photocatalytic coating liquid comprising a photocatalyst and an aqueous silicic acid solution, The aqueous silicic acid solution contains an alkali silicate and an aqueous solvent, Silicic acid concentration (SiO2 equivalent): 0.1 to 3 mass% Molar ratio of silicon (SiO2 equivalent) to alkali X (SiO2 / X): 85-10,000 Viscosity at 25℃ is 1 to 50 mPa s The photocatalytic coating liquid is an aqueous solution of silicic acid. [5] The photocatalytic coating liquid according to [4], further comprising a surfactant. [6] The photocatalytic coating liquid according to [4] or [5], wherein the aqueous solvent is a mixed solvent of water and a hydrophilic organic solvent. [7] A member having a coating film on its surface, the coating film being produced from the liquid according to any one of [1] to [6]. Effect of the Invention
[0014] The aqueous silicic acid solution of the present invention has superior coating properties compared to conventional silicon compound-based binders, and can easily produce photocatalytic films and undercoats with high transparency and water resistance. Therefore, the aqueous silicic acid solution of the present invention is useful when forming photocatalytic films on various members used in practical environments where rapid cleaning of the substrate surface is required. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] The present invention relates to an aqueous silicic acid solution for undercoating a photocatalyst film (undercoat liquid) or a photocatalyst coating liquid, which contains an aqueous silicic acid solution suitable as an undercoat of a photocatalyst film and as a binder for a photocatalyst. First, an aqueous silicic acid solution for undercoating a photocatalyst film (undercoat liquid) which is one embodiment of the present invention will be described.
[0017] <Aqueous solution of silicic acid for undercoating photocatalytic membranes (undercoat liquid)> The aqueous silicic acid solution for undercoating a photocatalyst film of the present invention contains an alkali silicate and an aqueous solvent, Silicic acid concentration (SiO2 equivalent): 0.1 to 3 mass% Molar ratio of silicon (SiO2 equivalent) to alkali X (SiO2 / X): 85-10,000 Viscosity at 25℃ is 1 to 50 mPa s It is. The aqueous silicic acid solution of the present invention can be used as an undercoat solution for a photocatalytic film. The undercoat solution in the present invention is applied to the surface of a substrate that may be deteriorated by photocatalytic action to form an undercoat, thereby preventing the deterioration of the substrate surface caused by the photocatalytic film.
[0018] <Alkaline silicate> The aqueous silicic acid solution of the present invention contains an alkali silicate in an aqueous solvent such that the molar ratio of silicon to alkali is specified.
[0019] As the alkali silicate in the present invention, various known alkali silicates can be used. For example, alkali metal silicates such as sodium silicate, potassium silicate, lithium silicate, etc.; alkaline earth metal silicates such as calcium silicate, magnesium silicate, etc. may be used alone or in combination of two or more of these. Among them, it is preferable to use sodium silicate, which is easy to obtain and handle.
[0020] The molar ratio (SiO2 / X) of silicon (SiO2 equivalent) of the alkali silicate in the aqueous silicic acid solution to the alkali X is 85 to 10,000, preferably 100 to 5,000, and more preferably 100 to 2,500. If the molar ratio exceeds 10,000, the stability of the solution may decrease and a great deal of effort may be required to remove the alkali, and if the molar ratio is less than 85, the transparency and water resistance of the coating film may decrease. The alkali X is preferably an alkali metal or an alkaline earth metal. In order to bring the molar ratio (SiO2 / X) of silicon in the alkali silicate to alkali X in the silicic acid aqueous solution into the range of 85 to 10,000, the parameters of the method for removing the alkali component of the alkali silicate can be adjusted. For example, the amount of ion exchange resin added in the ion exchange method, the current density and treatment time in the electrodialysis method, and the amount of aqueous solvent added during filtration in the membrane filtration method can be adjusted.
[0021] The viscosity of the aqueous silicic acid solution at 25° C. is 1 to 50 mPa·s, preferably 1.5 to 40 mPa·s, and more preferably 3 to 20 mPa·s. If the viscosity of the aqueous silicic acid solution at 25° C. is less than 1 mPa·s, the coatability may be insufficient, whereas if it exceeds 50 mPa·s, the stability of the aqueous silicic acid solution may decrease. The viscosity of the aqueous silicic acid solution at 25° C. may be measured using any device capable of measuring the viscosity of Newtonian and non-Newtonian fluids, for example, a rotational viscometer or a vibration viscometer. In the present invention, the value measured using a tuning fork vibration viscometer is used. In order to adjust the viscosity of the aqueous silicic acid solution at 25° C. to within the range of 1 to 50 mPa·s, the aqueous silicic acid solution in which the concentration of silicic acid and the molar ratio of silicon to alkali X have been adjusted may be subjected to a heat treatment.
[0022] The silicic acid concentration in the silicic acid aqueous solution calculated as SiO2 is 0.1 to 3 mass%, preferably 0.2 to 2.5%, and more preferably 0.3 to 2%. If the silicic acid concentration in the silicic acid aqueous solution calculated as SiO2 is less than 0.1%, the coatability and thickness of the coating film may be insufficient, and if it exceeds 3%, the stability of the silicic acid aqueous solution may decrease. In order to adjust the silicic acid concentration in the aqueous silicic acid solution to 0.1 to 3 mass % in terms of SiO2, an alkali silicate having a known SiO2 concentration may be diluted with an aqueous solvent.
[0023] <Aqueous solvent> As the aqueous solvent in the present invention, water is preferably used, but a mixed solvent of water and a hydrophilic organic solvent mixed with water at any ratio may be used. As the water, for example, purified water such as filtered water, deionized water, distilled water, and pure water is preferable. In addition, as the hydrophilic organic solvent, for example, alcohols such as methanol, ethanol, and isopropanol; glycols such as ethylene glycol; and glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol-n-propyl ether can be mentioned. When a mixed solvent is used, the ratio of the hydrophilic organic solvent in the mixed solvent is preferably more than 0% by mass and 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.
[0024] <Surfactant> The surfactant in the present invention is an optional component that improves the coating property by adjusting the interfacial tension of the liquid to improve the wettability to the substrate, and examples thereof include anionic surfactants such as fatty acid sodium salts, alkylbenzenesulfonates, higher alcohol sulfates, and polyoxyethylene alkyl ether sulfates; cationic surfactants such as alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, and quaternary ammonium salts; amphoteric surfactants such as alkylamino fatty acid salts, alkylbetaines, and alkylamine oxides; modified silicone oils such as polyether-modified silicones, aralkyl-modified silicones, alkyl-modified silicones, and higher fatty acid ester-modified silicones; and nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, alkyl glucosides, polyoxyethylene fatty acid esters, sucrose fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, fatty acid alkanolamides, and acetylene-based surfactants. Among these, nonionic surfactants are preferred from the viewpoint of the stability of the coating liquid. Moreover, the surfactant preferably has an HLB (Griffin method) of 7 to 18, more preferably 10 to 15. Of these, acetylene-based surfactants and polyether-modified silicone-based surfactants, which exhibit good properties as aqueous surfactants, are preferred.
[0025] The acetylene-based surfactant is acetylene glycol or an alkoxylated product of acetylene glycol, and more preferably one represented by the following general formula: R 1 -C≡CR 2 R 1 and R 2 are each independently a monovalent organic group, preferably a hydrocarbon group having 1 to 20 carbon atoms in which some of the hydrogen atoms of the hydrocarbon group are substituted with OH groups, or R 1 and R 2may have an ether bond in which a part of the hydrocarbon group having 1 to 20 carbon atoms contains an alkoxy group having 1 to 5 carbon atoms. Examples of the acetylene-based surfactant include Olfine EXP4001, EXP4200, EXP4123, and EXP4300 (manufactured by Nissin Chemical Industry Co., Ltd.).
[0026] The polyether-modified silicone surfactant is preferably a side-chain type in which a polyoxyalkylene group is introduced into the side chain of the silicone chain that serves as the main chain. Examples of side-chain type polyether-modified silicones include KF-351A, KF-353, KF-355A, KF-615A, KF-640, KF-642, KF-643, KF-644, KF-6204, and KF-6011 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0027] When a surfactant is added to the aqueous silicic acid solution of the present invention, the amount added is preferably 0.001 to 1.0% by mass, more preferably 0.005 to 0.2% by mass, and even more preferably 0.01 to 0.1% by mass relative to the aqueous silicic acid solution. If the amount of the surfactant added to the aqueous silicic acid solution is less than 0.001% by mass, the coatability may not be sufficiently improved, and if it exceeds 1.0% by mass, the durability of the film obtained from the aqueous silicic acid solution may decrease.
[0028] In order to improve adhesion to the substrate and durability, the aqueous silicic acid solution for undercoating the photocatalyst film (undercoat liquid) may further contain metal compounds including aluminum, titanium, zirconium, etc.; organic resins such as fluorine-based resins, acrylic resins, and urethane resins. However, these optional components are added within the range in which the aqueous silicic acid solution satisfies the above-mentioned silicic acid concentration, molar ratio of silicon to alkali X, and viscosity.
[0029] Next, a photocatalytic coating liquid according to another embodiment of the present invention will be described.
[0030] <Photocatalytic coating liquid> The photocatalytic coating liquid of the present invention contains a photocatalyst and a silicic acid aqueous solution. The silicic acid aqueous solution contained in the photocatalytic coating liquid contains an alkali silicate and an aqueous solvent, similar to the silicic acid aqueous solution for undercoating the photocatalytic film. Silicic acid concentration (SiO2 equivalent): 0.1 to 3 mass% Molar ratio of silicon (SiO2 equivalent) to alkali X (SiO2 / X): 85-10,000 Viscosity at 25℃ is 1 to 50 mPa s It is. That is, the aqueous silicic acid solution for undercoat of the photocatalyst film of the present invention can be used as a binder of the photocatalyst coating liquid. The photocatalyst coating liquid in the present invention is applied to a substrate to form a photocatalyst film, and contains at least a photocatalyst and the aqueous silicic acid solution of the present invention. <Photocatalyst> Photocatalyst is a general term for a substance that exhibits photocatalytic activity when irradiated with light having energy equal to or greater than a certain band gap. As such a substance, one or more of known metal oxide semiconductor particles, such as titanium oxide, tungsten oxide, zinc oxide, tin oxide, iron oxide, bismuth oxide, bismuth vanadate, and strontium titanate, can be used in combination. Among them, it is preferable to use titanium oxide particles, which have a particularly high photocatalytic activity under irradiation with light including ultraviolet light of 400 nm or less, are chemically stable, and are relatively easy to synthesize into nano-sized particles and disperse in a solvent.
[0031] <Titanium oxide particles> The titanium oxide particles themselves are not particularly limited, and any titanium oxide particles used as a photocatalyst can be used.
[0032] Generally, three types of crystalline phases of titanium oxide particles are known: rutile type, anatase type, and brookite type, and the titanium oxide particles of the present invention are preferably mainly of anatase type or rutile type. Note that "mainly" here means that titanium oxide particles of the crystalline phase are contained in the entire titanium oxide particles at 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and may be 100% by mass.
[0033] In order to enhance the photocatalytic activity of the titanium oxide particles, those which support metal compounds such as platinum, gold, palladium, iron, copper, and nickel, and those which contain nonmetallic components such as nitrogen, carbon, and sulfur, and those which form solid solutions with metal components such as tin, vanadium, chromium, manganese, niobium, molybdenum, rhodium, antimony, tungsten, and cerium can also be used.
[0034] In this specification, the term "solid solution" refers to a phase in which atoms at the lattice points of a certain crystal phase are replaced by other atoms, or other atoms enter the lattice gaps, i.e., a mixed phase in which another substance is considered to have been dissolved in a certain crystal phase, and refers to a homogeneous crystal phase. A solid solution in which solvent atoms at the lattice points are replaced by solute atoms is called a substitutional solid solution, and a solid solution in which solute atoms enter the lattice gaps is called an interstitial solid solution, and both are referred to in this specification.
[0035] The method for dissolving a different metal in a metal oxide crystal is not particularly limited, but examples include gas phase methods (CVD method, PVD method, etc.), liquid phase methods (hydrothermal method, sol-gel method, etc.), and solid phase methods (high temperature firing method, etc.).
[0036] <Titanium oxide particle dispersion liquid> The titanium oxide particles are preferably dispersed in an aqueous dispersion medium. As the aqueous dispersion medium, water is preferably used, but a mixed solvent of water and a hydrophilic organic solvent mixed with water at any ratio may be used. As the water, for example, purified water such as filtered water, deionized water, distilled water, and pure water is preferable. As the hydrophilic organic solvent, for example, alcohols such as methanol, ethanol, and isopropanol; glycols such as ethylene glycol; and glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol-n-propyl ether are preferable. When a mixed solvent is used, the ratio of the hydrophilic organic solvent in the mixed solvent is preferably more than 0% by mass and 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.
[0037] The dispersed particle diameter of titanium oxide particles in the titanium oxide particle dispersion liquid is the volume-based 50% cumulative distribution diameter (hereinafter referred to as D 50 The average particle size (sometimes referred to as "average particle size") is preferably 5 to 30 nm. This is because if the average particle size is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 30 nm, the dispersion and the photocatalytic film obtained by using the dispersion may become opaque.
[0038] In addition, the 90% cumulative distribution diameter (D 90 The diameter of the particle diameter (sometimes denoted as D) is preferably 5 to 100 nm, and more preferably 5 to 80 nm. 90 However, if it is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 100 nm, the dispersion and the photocatalytic film obtained by using it may become opaque. In addition, the D of the titanium oxide particles 50 and D. 90 As an apparatus for measuring the amount of fluorine, for example, ELSZ-2000ZS (manufactured by Otsuka Electronics Co., Ltd.), Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.), LA-910 (manufactured by Horiba, Ltd.), etc. can be used.
[0039] Titanium oxide particles are D 50 and D. 90 It is preferable that the particles have a molecular weight within the above range, because a dispersion having high photocatalytic activity and high transparency and a photocatalytic film obtained from the dispersion can be obtained.
[0040] Examples of such titanium oxide photocatalysts include anatase titanium oxide particles whose surfaces are modified with peroxo groups (JP Patent Publication No. 10-67516), titanium oxide particles in which tin and a transition metal that enhances visible light activity are dissolved and in which iron and silicon are attached to the surface (JP Patent Publication No. 2021-175697).
[0041] The concentration of titanium oxide particles in the titanium oxide particle dispersion is preferably 0.01 to 20% by mass, and particularly preferably 0.5 to 10% by mass, from the viewpoint of ease of producing a photocatalytic film of a required thickness.
[0042] <Silicate aqueous solution> The aqueous silicic acid solution contained in the photocatalytic coating liquid contains an alkali silicate in an aqueous solvent such that silicon and alkali have a specific molar ratio.
[0043] <Alkaline silicate> As the alkali silicate, various known alkali silicates can be used. For example, alkali metal silicates such as sodium silicate, potassium silicate, and lithium silicate; alkaline earth metal silicates such as calcium silicate and magnesium silicate can be used alone or in combination of two or more of these. Among them, it is preferable to use sodium silicate, which is easy to obtain and handle.
[0044] The molar ratio (SiO2 / X) of silicon (SiO2 equivalent) of the alkali silicate in the aqueous silicic acid solution to the alkali X is 85 to 10,000, preferably 100 to 5,000, and more preferably 100 to 2,500. If the molar ratio exceeds 10,000, the stability of the solution may decrease and a great deal of effort may be required to remove the alkali, and if the molar ratio is less than 85, the transparency and water resistance of the coating film may decrease. The alkali X is preferably an alkali metal or an alkaline earth metal. In order to set the molar ratio (SiO2 / X) of the silicon in the alkali silicate to the alkali X in the silicic acid aqueous solution within the range of 85 to 10,000, it may be adjusted by an ion exchange method that adsorbs and removes the alkali X, an electrodialysis method using an ion exchange membrane, an ultrafiltration membrane, a reverse osmosis membrane, or the like.
[0045] The viscosity of the aqueous silicic acid solution at 25° C. is 1 to 50 mPa·s, preferably 1.5 to 40 mPa·s, and more preferably 3 to 20 mPa·s. If the viscosity of the aqueous silicic acid solution at 25° C. is less than 1 mPa·s, the coatability may be insufficient, whereas if it exceeds 50 mPa·s, the stability of the aqueous silicic acid solution may decrease. In order to adjust the viscosity of the aqueous silicic acid solution at 25° C. to within the range of 1 to 50 mPa·s, the aqueous silicic acid solution in which the concentration of silicic acid and the molar ratio of silicon to alkali X have been adjusted may be subjected to a heat treatment.
[0046] The silicic acid concentration in the silicic acid aqueous solution calculated as SiO2 is 0.1 to 3 mass%, preferably 0.2 to 2.5%, and more preferably 0.3 to 2%. If the silicic acid concentration in the silicic acid aqueous solution calculated as SiO2 is less than 0.1%, the coatability and thickness of the coating film may be insufficient, and if it exceeds 3%, the stability of the silicic acid aqueous solution may decrease. In order to adjust the silicic acid concentration in the aqueous silicic acid solution to 0.1 to 3 mass % in terms of SiO2, an alkali silicate having a known SiO2 concentration may be diluted with an aqueous solvent.
[0047] <Aqueous solvent> As the aqueous solvent, water is preferably used, but a mixed solvent of water and a hydrophilic organic solvent mixed with water at any ratio may be used. As the water, for example, purified water such as filtered water, deionized water, distilled water, and pure water is preferable. In addition, as the hydrophilic organic solvent, for example, alcohols such as methanol, ethanol, and isopropanol; glycols such as ethylene glycol; and glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol-n-propyl ether can be mentioned. When a mixed solvent is used, the ratio of the hydrophilic organic solvent in the mixed solvent is preferably more than 0% by mass and 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.
[0048] <Surfactant> The surfactant is an optional component that improves the coating property by adjusting the interfacial tension of the liquid to improve the wettability to the substrate, and examples thereof include anionic surfactants such as fatty acid sodium salts, alkylbenzenesulfonates, higher alcohol sulfates, and polyoxyethylene alkyl ether sulfates; cationic surfactants such as alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, and quaternary ammonium salts; amphoteric surfactants such as alkylamino fatty acid salts, alkylbetaines, and alkylamine oxides; modified silicone oils such as polyether-modified silicones, aralkyl-modified silicones, alkyl-modified silicones, and higher fatty acid ester-modified silicones; and nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, alkyl glucosides, polyoxyethylene fatty acid esters, sucrose fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, fatty acid alkanolamides, and acetylene-based surfactants. Among these, nonionic surfactants are preferred from the viewpoint of the stability of the coating liquid. Moreover, the surfactant preferably has an HLB (Griffin method) of 7 to 18, more preferably 10 to 15. Of these, acetylene-based surfactants and polyether-modified silicone-based surfactants, which exhibit good properties as aqueous surfactants, are preferred.
[0049] The acetylene-based surfactant is acetylene glycol or an alkoxylated product of acetylene glycol, and more preferably one represented by the following general formula: R 1 -C≡CR 2 R 1 and R 2 are each independently a monovalent organic group, preferably a hydrocarbon group having 1 to 20 carbon atoms in which some of the hydrogen atoms of the hydrocarbon group are substituted with OH groups, or R 1 and R 2 may have an ether bond in which a part of the hydrocarbon group having 1 to 20 carbon atoms contains an alkoxy group having 1 to 5 carbon atoms. Examples of the acetylene-based surfactant include Olfine EXP4001, EXP4200, EXP4123, and EXP4300 (manufactured by Nissin Chemical Industry Co., Ltd.).
[0050] The polyether-modified silicone surfactant is preferably a side-chain type in which a polyoxyalkylene group is introduced into the side chain of the silicone chain that serves as the main chain. Examples of side-chain type polyether-modified silicones include KF-351A, KF-353, KF-355A, KF-615A, KF-640, KF-642, KF-643, KF-644, KF-6204, and KF-6011 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0051] When a surfactant is added to the aqueous silicic acid solution, the amount added is preferably 0.001 to 1.0% by mass, more preferably 0.005 to 0.2% by mass, and even more preferably 0.01 to 0.1% by mass relative to the aqueous silicic acid solution. If the amount of the surfactant added to the aqueous silicic acid solution is less than 0.001% by mass, the coatability may not be sufficiently improved, and if it exceeds 1.0% by mass, the durability of the film obtained from the aqueous silicic acid solution may decrease.
[0052] In order to improve adhesion to the substrate and durability, the photocatalytic coating liquid may further contain metal compounds containing aluminum, titanium, zirconium, etc., and organic resins such as fluorine-based resins, acrylic resins, and urethane resins. However, these optional components are added within the range in which the aqueous silicic acid solution satisfies the above-mentioned silicic acid concentration, molar ratio of silicon to alkali X, and viscosity.
[0053] The dispersed particle diameter of titanium oxide particles in the photocatalytic coating solution is the 50% cumulative distribution diameter (hereinafter referred to as D 50 The average particle size (sometimes referred to as "average particle size") is preferably 5 to 50 nm, and more preferably 5 to 30 nm. This is because if the average particle size is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 50 nm, the coating liquid and the photocatalytic film obtained by using the same may become opaque.
[0054] In addition, the 90% cumulative distribution diameter (D 90 The diameter of the particle diameter (sometimes denoted as D) is preferably 5 to 100 nm, and more preferably 5 to 80 nm. 90 However, if it is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 100 nm, the coating liquid and the photocatalytic film obtained by using it may become opaque. In addition, the D of the titanium oxide particles 50 and D. 90 The above-mentioned device can be used to measure the above.
[0055] The mass ratio of titanium oxide particles to the aqueous silicic acid solution as a binder [titanium oxide particles / silicic acid (SiO2 equivalent)] is preferably in the range of 0.01 to 99, more preferably 0.01 to 9, and even more preferably 0.01 to 2.5. This is because, if the mass ratio exceeds 99, the adhesion of the titanium oxide particles to the surfaces of various substrates may be insufficient, and, if it is less than 0.01, the photocatalytic activity may be insufficient.
[0056] Next, a method for producing the aqueous silicic acid solution for use as an undercoat for the photocatalyst film of the present invention or the aqueous silicic acid solution contained as a binder in the photocatalyst coating liquid of the present invention will be described.
[0057] <Method of producing silicic acid aqueous solution> The method for producing an aqueous silicic acid solution of the present invention comprises the following steps (1) to (3). (1) A process for producing an aqueous solution of alkali silicate from alkali silicate and water (2) A process for removing alkali from the aqueous alkali silicate solution (3) A process of heating the silicic acid aqueous solution from which the alkali has been removed and then cooling it. Each step will be described in detail below.
[0058] ·Process (1) In step (1), an aqueous solution of an alkali silicate is produced by mixing an alkali silicate with water. As the alkali silicate, various known alkali silicates can be used. For example, alkali metal silicates such as sodium silicate, potassium silicate, and lithium silicate; alkaline earth metal silicates such as calcium silicate and magnesium silicate can be used alone or in combination of two or more of these. Among them, it is preferable to use sodium silicate, which is easy to obtain and handle. The aqueous alkali silicate solution prepared in step (1) preferably has a SiO2 concentration of 0.1 to 3.0 mass %, more preferably 0.2 to 2.5 mass %, and even more preferably 0.3 to 2 mass %. The SiO2 concentration can be known by using sodium silicate with a known concentration, but it can also be measured using other general quantitative methods for metal components. For example, the Si concentration can be quantified using a calibration curve method using an ICP emission spectrometer or X-ray fluorescence spectrometer, and then converted into SiO2.
[0059] ·Process (2) In step (2), the alkaline component is removed from the aqueous alkali silicate solution. The method for removing the alkaline component is not limited as long as it can remove the alkaline component from the alkali silicate, and for example, an ion exchange method using an ion exchange resin, an electrodialysis method using an ion exchange membrane, a membrane filtration method using an ultrafiltration membrane, a reverse osmosis membrane, etc. can be used. The removal method may be selected from the above, but the ion exchange method is particularly good, and it is preferable to use an acrylic or styrene resin as the ion exchange resin. In addition, it is preferable that the ion exchange resin is an acidic resin into which a sulfo group or a carboxyl group has been introduced. The method for removing the alkaline components will be described in more detail below, taking the ion exchange method as an example. To the aqueous alkali silicate solution prepared in step (1), an ion exchange resin is added in an amount sufficient to remove the alkaline components. The aqueous alkali silicate solution to which the ion exchange resin has been added is then stirred, for example, for 15 minutes to 1 hour, and the ion exchange resin is filtered off to remove the alkaline ions.
[0060] ·Process (3) In step (3), the silicic acid aqueous solution from which the alkaline components have been removed is heated to increase its viscosity, and then cooled to stop the increase in viscosity. Increasing the viscosity of the silicic acid aqueous solution can improve its coatability. When heated, the silicic acid aqueous solution gels and becomes colloidal in a short period of time, making it unusable as an undercoat or photocatalyst binder. Therefore, after increasing the viscosity to a specified level, the solution is cooled and stabilized.
[0061] The heating temperature is 30 to 80°C, preferably 40 to 60°C, from the viewpoint of viscosity control. This is because if the heating temperature is less than 30°C, it may take a long time to increase the viscosity, and if it exceeds 80°C, the viscosity increases in a short time, making control difficult. The heating time is adjusted so that the viscosity falls within the above-mentioned range (viscosity at 25°C is 1 to 50 mPa·s), and is preferably 1 minute to 8 hours. The cooling temperature is appropriately 30°C or lower. This is because if the cooling temperature exceeds 30°C, the effect of suppressing the progress of gelation and colloidization of the silicic acid aqueous solution may be reduced. The liquid can be further stabilized by cooling and diluting the aqueous silicic acid solution with water and / or a hydrophilic organic solvent to reduce the silicic acid concentration. The water and / or hydrophilic organic solvent can be the same as those described above. The aqueous silicic acid solution obtained by the above steps can be used as an aqueous silicic acid solution for undercoating the photocatalyst film of the present invention.
[0062] <Method of manufacturing photocatalyst coating liquid> The method for producing the photocatalytic coating liquid of the present invention includes, for example, a method of mixing the aqueous silicic acid solution obtained by the above steps (1) to (3) with the titanium oxide particle dispersion obtained by the following steps (4) to (6).
[0063] (4) A process for producing a peroxotitanic acid solution from a raw material titanium compound, a basic substance, hydrogen peroxide, and an aqueous dispersion medium. (5) A process for heating the peroxotitanic acid solution produced in the above process (4) at 80 to 250° C. under pressure control to obtain a titanium oxide particle dispersion liquid. (6) A step of mixing the titanium oxide particle dispersion liquid obtained in the step (5) with the aqueous silicic acid solution obtained in the steps (1) to (3). Each step will be described in detail below.
[0064] ·Process (4): In step (4), a peroxotitanic acid solution is produced by reacting a starting titanium compound, a basic substance, and hydrogen peroxide in an aqueous dispersion medium. More specifically, a basic substance is added to the raw material titanium compound in an aqueous dispersion medium to form titanium hydroxide, impurity ions other than the metal ions contained therein are removed, and hydrogen peroxide is added to obtain a peroxotitanic acid solution.
[0065] Here, examples of the raw titanium compound include inorganic acid salts such as titanium chloride, nitrate, and sulfate, organic acid salts such as formic acid, citric acid, oxalic acid, lactic acid, and glycolic acid, and titanium hydroxide precipitated by hydrolysis of an aqueous solution of these salts with an alkali, and these may be used alone or in combination of two or more. Among these, it is preferable to use titanium chloride (TiCl3, TiCl4).
[0066] In the present invention, the aqueous dispersion medium can be any of those mentioned above, and is used in such a manner as to obtain the above-mentioned composition. The concentration of the aqueous titanium compound solution formed from the titanium compound and the aqueous dispersion medium is preferably 60% by mass or less, particularly 30% by mass or less. The lower limit of the concentration can be appropriately selected, but is usually preferably 1% by mass or more.
[0067] The basic substance is used to smoothly convert the raw titanium compound into titanium hydroxide, and examples of the basic substance include hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide and potassium hydroxide, ammonia, and amine compounds such as alkanolamines and alkylamines, of which ammonia is particularly preferred and is added in an amount that adjusts the pH of the aqueous solution of the raw titanium compound to 7 or more, particularly 7 to 10. The basic substance may be used in the form of an aqueous solution of an appropriate concentration together with the aqueous dispersion medium. Hydrogen peroxide is used to convert the raw titanium compound or titanium hydroxide into peroxotitanium, that is, a titanium oxide compound containing Ti-OO-Ti bonds, and is usually used in the form of aqueous hydrogen peroxide. The amount of hydrogen peroxide added is preferably 1.5 to 20 times the molar amount of Ti, or the total amount of Ti, transition metal, and Sn. In the reaction of converting the raw titanium compound or titanium hydroxide into peroxotitanic acid by adding hydrogen peroxide, the reaction temperature is preferably 5 to 80°C, and the reaction time is preferably 30 minutes to 24 hours.
[0068] The peroxotitanic acid solution thus obtained may contain an alkaline substance or an acidic substance for adjusting the pH, etc. Examples of the alkaline substance include ammonia, sodium hydroxide, calcium hydroxide, alkylamines, etc., and examples of the acidic substance include inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, carbonic acid, phosphoric acid, hydrogen peroxide, etc., and organic acids such as formic acid, citric acid, oxalic acid, lactic acid, glycolic acid, etc. In this case, the pH of the obtained peroxotitanic acid solution is preferably 1 to 9, particularly 4 to 7, from the viewpoint of safety in handling.
[0069] ·Process (5): In step (5), the peroxotitanic acid solution obtained in step (4) is subjected to a hydrothermal reaction under pressure control at a temperature of 80 to 250°C, preferably 100 to 250°C, for 0.01 to 24 hours. The reaction temperature is preferably 80 to 250°C from the viewpoints of reaction efficiency and reaction controllability, and as a result, peroxotitanic acid is converted into titanium oxide particles. Here, "under pressure control" refers to maintaining the reaction temperature by applying appropriate pressure so that the reaction temperature can be maintained when the reaction temperature exceeds the boiling point of the dispersion medium, and includes controlling the reaction temperature at atmospheric pressure when the temperature is below the boiling point of the dispersion medium. The pressure used here is usually about 0.12 to 4.5 MPa, preferably about 0.15 to 4.5 MPa, and more preferably about 0.20 to 4.5 MPa. The reaction time is preferably 1 minute to 24 hours. A titanium oxide particle dispersion liquid is obtained by this step (5).
[0070] The pH of the titanium oxide particle dispersion obtained in step (5) is preferably 7 to 14, and more preferably 9 to 14. The titanium oxide particle dispersion obtained in step (2) may contain an alkaline substance or an acidic substance for adjusting the pH to the above-mentioned pH, and the alkaline substance, acidic substance, and method for adjusting the pH are the same as those for the peroxotitanic acid solution obtained in the above-mentioned step (4).
[0071] The dispersed particle diameter of the titanium oxide particles obtained here (D 50 and D. 90 ) is preferably in the range as described above, and the particle diameter can be controlled by adjusting the reaction conditions. For example, the particle diameter can be reduced by shortening the reaction time or the temperature rise time.
[0072] The concentration of titanium oxide particles in the titanium oxide particle dispersion liquid thus produced can be calculated from the mass of the non-volatile matter (titanium oxide particles) obtained by sampling a portion of the titanium oxide particle dispersion liquid and volatilizing the solvent by heating at 105°C for 1 hour and the mass of the sampled titanium oxide particle dispersion liquid according to the following formula. Concentration of titanium oxide particle dispersion (%) = [mass of non-volatile matter (g) / mass of titanium oxide particle dispersion (g)] x 100
[0073] ·Process (6): In step (6), the titanium oxide particle dispersion liquid obtained in step (5) and the silicic acid aqueous solution obtained in steps (1) to (3) are mixed in the ratio described above (i.e., [titanium oxide particles / silicic acid (SiO2 equivalent)] is preferably 0.01 to 99, more preferably 0.01 to 9, and even more preferably 0.01 to 2.5). The mixing method is not particularly limited as long as the two types of liquids are mixed uniformly, and for example, they can be mixed by stirring using a commonly available stirrer. The temperature during mixing is 5 to 50°C, preferably 10 to 30°C, and the time is preferably 1 minute to 1 hour.
[0074] The total concentration of titanium oxide particles and silicic acid (SiO2 equivalent) in the photocatalytic coating liquid thus prepared is preferably 0.01 to 20 mass%, particularly preferably 0.5 to 10 mass%, from the viewpoint of ease of preparation of a photocatalytic film of a required thickness. Regarding concentration adjustment, if the concentration is higher than the desired concentration, it can be reduced by diluting it with an aqueous solvent, and if it is lower than the desired concentration, it can be increased by volatilizing or filtering off the aqueous solvent.
[0075] <Components having a coating film formed on the surface from a silicic acid solution or a photocatalytic coating liquid> The aqueous silicic acid solution for undercoat of photocatalyst film and the photocatalyst coating liquid of the present invention can be used to form undercoat or photocatalyst film on the surface of various members. Here, the various members are not particularly limited, but the materials of the members include, for example, organic materials and inorganic materials. These can have various shapes according to their respective purposes and uses.
[0076] Examples of organic materials include synthetic resin materials such as polyvinyl chloride resin (PVC), polyethylene (PE), polypropylene (PP), polycarbonate (PC), acrylic resin, polyacetal, fluororesin, silicone resin, ethylene-vinyl acetate copolymer (EVA), acrylonitrile-butadiene rubber (NBR), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyvinyl butyral (PVB), ethylene-vinyl alcohol copolymer (EVOH), polyimide resin, polyphenylene sulfide (PPS), polyetherimide (PEI), polyetheretherimide (PEEI), polyetheretherketone (PEEK), melamine resin, phenolic resin, acrylonitrile-butadiene-styrene (ABS) resin, natural materials such as natural rubber, or semi-synthetic materials of the above synthetic resin materials and natural materials. These may be commercialized into required shapes and configurations such as films, sheets, fiber materials, fiber products, other molded products, laminates, etc.
[0077] Examples of inorganic materials include non-metallic inorganic materials and metallic inorganic materials. Examples of non-metallic inorganic materials include glass, ceramics, and stone. These may be commercialized in various forms such as tiles, glass, mirrors, walls, and decorative materials. Examples of metallic inorganic materials include cast iron, steel, iron, iron alloys, aluminum, aluminum alloys, nickel, nickel alloys, and zinc die-casting. These may be plated with the metallic inorganic materials, coated with the organic materials, or plated on the surface of the organic materials or non-metallic inorganic materials.
[0078] The aqueous silicic acid solution or photocatalytic coating liquid for undercoating a photocatalytic film of the present invention is particularly useful for producing a photocatalytic film by applying it to various members made of inorganic substances such as glass and metal, and organic substances such as resin, and is particularly useful for producing a transparent photocatalytic film on various substrates.
[0079] As a method for forming an undercoat or a photocatalyst film on the surface of various substrates, for example, an aqueous silicic acid solution or a photocatalyst coating liquid may be applied to the surface of the substrate by a known application method such as spray coating or dip coating, and then the solution may be dried by a known drying method such as far-infrared drying, IH drying or hot air drying. The thickness of the undercoat or the photocatalyst film may be selected from various thicknesses, but is usually preferably in the range of 10 nm to 10 μm. This forms the undercoat or photocatalytic coating described above.
[0080] The undercoat thus formed is transparent, and is capable of suppressing deterioration of the substrate caused by the photocatalytic action of the above-mentioned photocatalytic film, and of enhancing the adhesion between the substrate and the photocatalytic film.
[0081] The photocatalytic film formed in this manner is transparent and exhibits good photocatalytic action, particularly in the ultraviolet region (wavelength 10 to 400 nm). Various substrates on which the photocatalytic film is formed can exhibit cleaning, deodorizing, antibacterial, and other effects on the surface of the component due to the photocatalytic action of titanium oxide. EXAMPLES
[0082] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. Various evaluations in the present invention were carried out as follows.
[0083] (1) The 50% and 90% cumulative distribution diameters of titanium oxide particles in the liquid (D 50 and D. 90 ) D of titanium oxide particles in liquid 50 and D. 90 was calculated as the 50% and 90% cumulative distribution diameters on a volume basis measured by dynamic light scattering using a laser beam. Specifically, the photocatalyst coating liquid was measured using a particle size distribution analyzer (ELSZ-2000ZS, manufactured by Otsuka Electronics Co., Ltd.).
[0084] (2) Determination of concentrations of alkali metal ions and alkaline earth metal ions The concentrations of alkali metal ions and alkaline earth metal ions in the solution were evaluated by ion chromatography. Specifically, the silicic acid solution was appropriately diluted and filtered through a 0.2 μm filter, and then quantified using an ion chromatograph (930 Compact IC Flex, Metrohm) equipped with a cation analysis column, Metrosep C3 250 / 4.0, and an electric conductivity detector.
[0085] (3) Viscosity measurement of liquid The viscosity of the liquid was measured using a tuning fork vibro viscometer (SV-10, manufactured by A&D Co., Ltd.) after adjusting the liquid temperature to 25°C.
[0086] (4) Evaluation of the coatability of undercoat liquid or photocatalytic coating liquid on various substrates A surface of a substrate cut to A4 size (210mm x 297mm) was coated with 2g of liquid using a #7 wire bar coater, and the condition of the liquid film when spread and the coating film after drying for 30 minutes in an oven set at 80°C were visually evaluated according to the following criteria. Polyethylene terephthalate (PET) film and polyvinyl chloride (PVC) sheet were used as substrates for checking coatability. Liquid and coating film condition Very good (marked as ◎) The liquid film spreads over the entire surface and no cissing occurs on the coating. Good (marked as ○) The liquid film spreads over the entire surface, but cissing occurs at the edge of the coating film. · Poor (marked as ×) · The liquid film does not spread over the entire surface, and random cissing occurs on the coating film.
[0087] (5) Uniformity evaluation of undercoat or photocatalyst film The uniformity of the coating film formed on the PET film in (4) was evaluated by appearance (visual inspection) and fluorescent X-ray analysis. Specifically, the fluorescent X-ray intensity of Si was measured at five randomly selected points on the coating film, and the ratio of the maximum value to the minimum value (maximum value / minimum value) was used to evaluate the film according to the following criteria. The fluorescent X-ray intensity of Si was measured under vacuum conditions using an energy dispersive X-ray fluorescence analyzer (EDX-7000, Shimadzu Corporation). Very good (marked with ◎) The appearance is transparent, and the ratio of the maximum and minimum values of the fluorescent X-ray intensity of Si is 1.5 or less. Good (marked as ○): Transparent in appearance, with the ratio of maximum to minimum Si fluorescent X-ray intensity exceeding 1.5 and 2.0 or less · Poor (marked as ×) · Appearance is cloudy or the ratio of maximum to minimum Si fluorescent X-ray intensity exceeds 2.0
[0088] (6) Water resistance evaluation of undercoat or photocatalytic film The water resistance of the coating film prepared on the PET film in (4) was evaluated by the change in the fluorescent X-ray intensity of Si before and after immersion in pure water. Specifically, the fluorescent X-ray intensity of Si was measured before and after immersion in pure water (room temperature, 16 hours) at five points randomly selected from the coating film, and the Si residual rate at each point (fluorescent X-ray intensity of Si after immersion in pure water / fluorescent X-ray intensity of Si before immersion in pure water × 100) was calculated as the arithmetic mean value of the five points, and evaluated according to the following criteria. The fluorescent X-ray intensity of Si was measured using the same device as in (5). · Very good (marked as ◎) · The arithmetic mean of the Si residual rate is 98% or more · Good (marked as ○) · The arithmetic mean of the residual silicon rate is 95% or more and less than 98% · Poor (marked as ×) · The arithmetic mean of the Si remaining rate is less than 95%
[0089] (7) Identification of the crystalline phase of titanium oxide particles The crystalline phase of the titanium oxide particles was evaluated by powder X-ray diffraction. Specifically, the titanium oxide particle dispersion was dried at 105°C for 3 hours, and the titanium oxide particles were collected and analyzed by powder X-ray diffraction (D2 PHASER, Bruker AXS).
[0090] (8) Preparation of silicic acid aqueous solution / comparison sample [Preparation Example 1-1] 13.8 g of sodium silicate (JIS No. 3 sodium silicate, SiO2 concentration: 29 mass%, Na2O concentration: 9.5 mass%) was diluted with 186.2 g of pure water to obtain an aqueous sodium silicate solution with a SiO2 concentration of 2.0 mass%. To 200 g of this sodium silicate aqueous solution, 20 mL of strong acid cation exchange resin (Amberlite HPR1024H, Organo Corporation) was added and stirred for 15 minutes to obtain Na + After removing the ion exchange resin, the ion exchange resin was filtered off. The liquid was then heated to 40°C and stirred for 60 minutes, and then cooled to 25°C. To 99.95 g of the thus obtained liquid, 0.05 g of an acetylene-based surfactant (Olfine EXP.4200, manufactured by Nissin Chemical Industry Co., Ltd., HLB=10-13) was added to obtain an aqueous silicic acid solution (A) of the present invention.
[0091] [Preparation Example 1-2] 13.8 g of sodium silicate (JIS No. 3 sodium silicate, SiO2 concentration: 29 mass%, Na2O concentration: 9.5 mass%) was diluted with 186.2 g of pure water to obtain an aqueous sodium silicate solution with a SiO2 concentration of 2.0 mass%. To 200 g of this sodium silicate aqueous solution, 20 mL of strong acid cation exchange resin (Amberlite HPR1024H, Organo Corporation) was added and stirred for 15 minutes to obtain Na + After removing the ion exchange resin, the ion exchange resin was filtered off. The liquid was then heated to 40°C and stirred for 60 minutes, and then cooled to 25°C. To 24.99 g of the liquid thus obtained, 74.96 g of pure water and 0.05 g of a polyether-modified silicone surfactant (KF-643, Shin-Etsu Chemical Co., Ltd., HLB=14) were added to obtain an aqueous silicic acid solution (B) of the present invention.
[0092] [Preparation Example 1-3] An aqueous silicic acid solution (C) of the present invention was obtained in the same manner as in Preparation Example 1-1, except that the amount of the strongly acidic cation exchange resin added was 30 mL.
[0093] [Preparation Example 1-4] An aqueous silicic acid solution (D) of the present invention was obtained in the same manner as in Preparation Example 1-1, except that 19 mL of strongly acidic cation exchange resin was added, the heating time was 80 minutes, and no surfactant was added.
[0094] [Preparation Example 1-5] An aqueous silicic acid solution (E) of the present invention was obtained in the same manner as in Preparation Example 1-1, except that the amount of the strongly acidic cation exchange resin added was 40 mL.
[0095] [Preparation Example 1-6] An aqueous silicic acid solution (F) of the present invention was obtained in the same manner as in Preparation Example 1-1, except that the heating time was changed to 10 minutes.
[0096] [Preparation Example 1-7] 13.8 g of sodium silicate (JIS No. 3 sodium silicate, SiO2 concentration: 29 mass%, Na2O concentration: 9.5 mass%) was diluted with 186.2 g of pure water to obtain an aqueous sodium silicate solution with a SiO2 concentration of 2.0 mass%. To 200 g of this sodium silicate aqueous solution, 20 mL of strong acid cation exchange resin (Amberlite HPR1024H, Organo Corporation) was added and stirred for 15 minutes to obtain Na + After removing the ion exchange resin, the ion exchange resin was filtered off. The liquid was then heated to 40°C and stirred for 60 minutes, and then cooled to 25°C. To 24.99 g of the liquid thus obtained, 24.98 g of pure water, 49.98 g of ethanol, and 0.05 g of a surfactant (Olfine EXP.4200, manufactured by Nissin Chemical Industry Co., Ltd.) were added to obtain an aqueous silicic acid solution (G) of the present invention.
[0097] [Preparation Example 1-8] A comparative sample (H) was obtained in the same manner as in Preparation Example 1-1, except that the amount of the strongly acidic cation exchange resin added was 16 mL.
[0098] [Preparation Example 1-9] Comparative sample (I) was obtained in the same manner as in Preparation Example 1-1, except that the amount of strongly acidic cation exchange resin added was 18 mL.
[0099] [Preparation Example 1-10] Comparative sample (J) was obtained in the same manner as in Preparation Example 1-1, except that the heating time was 100 minutes. During heating, the transparency of the liquid decreased, and the progress of gelation was observed.
[0100] [Preparation Example 1-11] 34.4 g of sodium silicate (JIS No. 3 sodium silicate, SiO2 concentration: 29 mass%, Na2O concentration: 9.5 mass%) was diluted with 165.6 g of pure water to obtain an aqueous sodium silicate solution with a SiO2 concentration of 5.0 mass%. 50 mL of strong acid cation exchange resin (Amberlite HPR1024H, Organo Corporation) was added to 200 g of this sodium silicate aqueous solution and stirred for 15 minutes to obtain Na +After removing the ion exchange resin, the ion exchange resin was filtered off. The liquid was then heated to 40°C and stirred for 60 minutes, but the comparative sample (K) gelled and lost its fluidity, making it unusable as an undercoat liquid or photocatalyst coating liquid.
[0101] [Preparation Example 1-12] Colloidal silica (Snowtex 30, Nissan Chemical Industries, Ltd., SiO2 concentration: 30% by mass) (13.3 g) was diluted with pure water (186.7 g) to obtain a silica dispersion (L) with a SiO2 concentration of 2.0% by mass.
[0102] (9) Measurement results of silicic acid aqueous solution / comparison sample Table 1 shows the SiO2 concentration and Na + The concentration, SiO2 / Na molar ratio, and viscosity are shown.
[0103] [Table 1]
[0104] (10) Evaluation of the coating properties of the aqueous silicic acid solution / comparison sample and its coating film (undercoat) Table 2 shows the evaluation results of the PET film coatability, PVC sheet coatability, and the appearance, uniformity, and water resistance of the coating film when applied to the PET film for the liquid prepared in each preparation example.
[0105] [Table 2]
[0106] (11) Preparation of titanium oxide particle dispersion [Preparation Example 2-1] A 36% by mass titanium(IV) chloride aqueous solution was diluted 10 times with pure water, and then 10% by mass ammonia water was gradually added to neutralize and hydrolyze the solution, resulting in a titanium hydroxide precipitate. The pH at this time was 8.5. The precipitate was deionized by repeatedly adding pure water and decanting it. After this deionization, 35% by mass hydrogen peroxide water was added to the titanium hydroxide precipitate so that the H2O2 / Ti (molar ratio) was 8, and then the mixture was stirred at 60°C for 2 hours to fully react, resulting in an orange transparent peroxotitanic acid solution. A 500 mL autoclave was charged with 400 mL of peroxotitanic acid solution, which was subjected to hydrothermal treatment at 130° C. for 90 minutes. Thereafter, pure water was added to adjust the concentration, thereby obtaining a titanium oxide particle dispersion (a) (titanium oxide concentration: 1.0 mass %). 50 is 18 nm, D 90 The crystal phase was anatase type titanium oxide.
[0107] (12) Preparation of photocatalytic coating solution / comparison sample [Preparation Example 3-1] A photocatalytic coating liquid (α) was obtained by adding 100 g of pure water and 100 g of the titanium oxide particle dispersion liquid (a) to 100 g of the silicic acid aqueous solution (A).
[0108] [Preparation Example 3-2] A photocatalytic coating liquid (β) was obtained in the same manner as in Preparation Example 3-1, except that the aqueous silicic acid solution (C) was used.
[0109] [Preparation Example 3-3] A photocatalytic coating liquid (γ) was obtained in the same manner as in Preparation Example 3-1, except that the aqueous silicic acid solution (D) was used.
[0110] [Preparation Example 3-4] A photocatalytic coating liquid (δ) was obtained in the same manner as in Preparation Example 3-1, except that the aqueous silicic acid solution (E) was used.
[0111] [Preparation Example 3-5] A photocatalytic coating liquid (ε) was obtained in the same manner as in Preparation Example 3-1, except that the aqueous silicic acid solution (F) was used.
[0112] [Preparation Example 3-6] A photocatalytic coating liquid (ζ) was obtained by adding 25 g of the titanium oxide particle dispersion liquid (a) to 100 g of the silicic acid aqueous solution (G).
[0113] [Preparation Example 3-7] A comparative sample (η) was obtained in the same manner as in Preparation Example 3-1, except that the comparative sample (H) was used.
[0114] [Preparation Example 3-8] A comparative sample (θ) was obtained in the same manner as in Preparation Example 3-1, except that the comparative sample (I) was used.
[0115] [Preparation Example 3-9] Comparative sample (ι) was obtained in the same manner as in Preparation Example 3-1, except that comparative sample (J) was used.
[0116] [Preparation Example 3-10] A comparative sample (κ) was obtained in the same manner as in Preparation Example 3-1, except that the silica dispersion liquid (L) was used.
[0117] (13) Measurement results of photocatalytic coating liquid / comparison sample Table 3 shows the SiO2 concentration, TiO2 concentration, TiO2 / SiO2 (binder) mass ratio, and dispersed particle diameter of titanium oxide particles (D 50 , D 90 ) are shown below.
[0118] [Table 3]
[0119] (14) Evaluation of the coating properties of photocatalytic coating liquid / comparison samples and their coating films Table 4 shows the evaluation results of the PET film coatability, PVC sheet coatability, and the appearance, uniformity, and water resistance of the coating film when applied to the PET film for the liquid prepared in each preparation example.
[0120] [Table 4]
[0121] (15) Summary of evaluation results From the results of Examples and Comparative Examples 1, 2, 6, and 7, it was found that the undercoat made from a silicic acid aqueous solution with a small SiO2 / Na molar ratio was poor in water resistance, and that the photocatalytic coating solution prepared by mixing with a titanium oxide particle dispersion caused particle aggregation, resulting in a cloudy photocatalytic film.
[0122] From the results of the examples and comparative examples 3 and 8, it was found that the undercoat made from the highly viscous silicic acid aqueous solution that had undergone gelation had irregularities and low uniformity, and similarly, irregularities were observed in the photocatalytic film of the photocatalytic coating solution prepared by mixing with the titanium oxide particle dispersion.
[0123] From the results of the Example and Comparative Example 4, it is found that an aqueous solution of silicic acid with a high SiO2 concentration has low liquid stability and quickly gels when heated, and therefore cannot be used as an undercoat or photocatalyst coating liquid.
[0124] From the results of the Example and Comparative Examples 5 and 9, it is seen that the undercoat liquid consisting of a silica dispersion liquid and the photocatalyst coating liquid had poor coatability and uniformity of the coating film, and the undercoat also had poor water resistance.
Claims
1. Contains an alkali silicate and an aqueous solvent, Silicic acid concentration (SiO 2 (conversion): 0.1 to 3% by mass Silicon (SiO 2 (SiO 2 / X): 85-10,000 Viscosity at 25°C: 1 to 50 mPa·s This is an aqueous solution of silicic acid used as an undercoat for photocatalytic membranes.
2. The aqueous silicic acid solution according to claim 1 , further comprising a surfactant.
3. The aqueous silicic acid solution according to claim 1 or 2, wherein the aqueous solvent is a mixed solvent of water and a hydrophilic organic solvent.
4. A photocatalytic coating liquid comprising a photocatalyst and an aqueous silicic acid solution, The aqueous silicic acid solution contains an alkali silicate and an aqueous solvent, Silicic acid concentration (SiO 2 (conversion): 0.1 to 3% by mass Silicon (SiO 2 (SiO 2 / X): 85-10,000 Viscosity at 25°C: 1 to 50 mPa·s The photocatalytic coating liquid is an aqueous solution of silicic acid.
5. The photocatalytic coating liquid according to claim 4, further comprising a surfactant.
6. 6. The photocatalytic coating liquid according to claim 4, wherein the aqueous solvent is a mixed solvent of water and a hydrophilic organic solvent.
7. A member having a coating film formed on its surface from the liquid according to claim 1 or 4.
Citation Information
Patent Citations
Photocatalytic hydrophilic coating composition and method for preparing photocatalytic hydrophilic member
JP2001098187A
Aqueous coating material composition, and member having coating film formed therefrom
JP2003096394A
Method for producing tungsten oxide photocatalyst
JP2009148700A
Titanium oxide particle, dispersion thereof, photocatalyst thin film, member having photocatalyst thin film on its surface, and method for producing titanium oxide particle dispersion
JP2021175697A